2018
DOI: 10.1200/jgo.17.00147
|View full text |Cite
|
Sign up to set email alerts
|

Data Reliability and Coding Completeness of Cancer Registry Information Using Reabstracting Method in the National Cancer Institute: Thailand, 2012 to 2014

Abstract: PurposeData quality is a core value of cancer registries, which bring about greater understanding of cancer distribution and determinants. Thailand established its cancer registry in 1986; however, studies focusing on data reliability have been limited. This study aimed to assess the coding completeness and reliability of the National Cancer Institute (NCI) hospital-based cancer registry, Thailand.MethodsThis study was conducted using the reabstracting method. We focused on seven cancer sites—the colon, rectum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Despite this slight shortfall, the registry's overall competence performance remains creditable. Similar to the previous studies in Thailand (32) and India (33) which also found high percent of completeness of data above ninety percent. The study in Finland presented a hundred percent complete of the records was higher as compared to the current findings (34).…”
Section: Discussionsupporting
confidence: 90%
“…Despite this slight shortfall, the registry's overall competence performance remains creditable. Similar to the previous studies in Thailand (32) and India (33) which also found high percent of completeness of data above ninety percent. The study in Finland presented a hundred percent complete of the records was higher as compared to the current findings (34).…”
Section: Discussionsupporting
confidence: 90%
“…We though believe that our data give a realistic estimate of the order of magnitude of the issue. d. Furthermore, these results may have been influenced by documentation disparities, which have been demonstrated to occur in a significant number of patients in similar studies [9,[42][43][44][45][46][47][48][49]. e. We have no data to estimate to which extent complications emerging in the course of treatment might have influenced the results of this study, though e.g.…”
Section: Discussionmentioning
confidence: 84%
“…We chose to compare incident malignancy rates between our KTRs and the Thai general population between 2013 and 2015. We only selected the 2013–2015 period because the place of residence to be matched with that of our KTRs in the registry had been validated by cross-checking with the Ministry of Interior’s National Civil Registration records [ 9 ]. Additionally, data after 2016 were not available when we conducted the analysis.…”
Section: Methodsmentioning
confidence: 99%